Eloquent Sedition: Notes toward a Genealogy of Dissidence - Timothy Hampton (Les Dossiers du GRIHL)
This essay argues that the emergence of a tradition of “dissident” writing in the sixteenth-century in France goes hand-in-hand with a reflection on the limits and dangers of what was called, during the period, “sedition.” Sedition is the twin or double of dissidence, and dissident writing simultaneously acknowledges the power of seditious action and helps to make it coherent by setting it into literary form. The argument includes analysis of texts by Rabelais, Luther, Guevara, and La Noue.